Research on the Present Situation, Problems and Countermeasures of Digital Transformation of Small and Medium-sized Private Enterprises - Yue, Weihao (Transactions on Economics, Business and Management Research, 2024)
In recent years, the digital transformation of small and medium-sized private enterprises has become one of the hot issues of academic and industrial concern. This paper first expounds the development status and existing problems of digital transformation of small and medium-sized private enterprises, then analyzes the digital transformation of small and medium-sized private enterprises by SWOT analysis and PEST analysis model, and finally puts forward some countermeasures and suggestions at the government level, enterprise level and market level.